2020
DOI: 10.1002/oby.22996
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity, the Home Food Environment, and Parent Feeding Practices in the Era of COVID‐19

Abstract: Objective This study aimed to describe changes in families’ home food environment and parent feeding practices, from before to during the coronavirus disease 2019 (COVID‐19) pandemic, and examine whether changes differed by food security status. Methods Parents (N = 584) in the US completed a single online survey, reporting on food security, home food availability, and feeding practices both retrospectively (considering before COVID‐19) and currently (during COVID‐19). χ2 and univariate regressions examined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
290
1
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(335 citation statements)
references
References 40 publications
29
290
1
15
Order By: Relevance
“…The COVID pandemic has specifically highlighted the influence food insecurity can have on parent feeding practices. Compared to families with food security, parents experiencing food insecurity increased the frequency at which they pressured their children to eat during the COVID pandemic [ 64 ]. While the long-term impact of changes in parent feeding practices during this time are unknown, changes in parent feeding practices in response to growing food insecurity due to the COVID pandemic are demonstrative of the nuanced ways in which this period may have lasting implications for child health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID pandemic has specifically highlighted the influence food insecurity can have on parent feeding practices. Compared to families with food security, parents experiencing food insecurity increased the frequency at which they pressured their children to eat during the COVID pandemic [ 64 ]. While the long-term impact of changes in parent feeding practices during this time are unknown, changes in parent feeding practices in response to growing food insecurity due to the COVID pandemic are demonstrative of the nuanced ways in which this period may have lasting implications for child health.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence regarding the relationship between food insecurity and pressure to eat has also been mixed. Food insecurity has been associated with greater pressure to eat in some studies [ 59 , 62 , 63 , 64 ] and no association in others [ 58 , 61 ]. In food secure households, pressure to eat has had a positive association with child vegetable consumption but not in households experiencing food insecurity [ 65 ].…”
Section: Structural Constraints Impact Parent Feeding Practicesmentioning
confidence: 99%
“…Moreover, an increase in snacks, sugared fruit juices, and soft drinks consumption was reported. Another online survey, performed in the USA during the months of April and May 2020 on 584 parents with children, found a 17% overall decrease of food-secure families and a 20% increase of families experiencing very low food security since the beginning of the pandemic; moreover, about one-third of the families reported an increase in the amount of high-calorie snack foods and desserts/sweets during the same period [ 54 ]. An Italian study including 41 children and adolescents with obesity found that the analyzed subjects consumed more potato chips, red meat, sugary drinks, but also fruit, after 3 weeks of mandatory stay-at-home confinement during the pandemic [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of the COVID-19 pandemic, a new set of challenges for households to maintain a healthy and varied diet have arisen (10) . Only a handful of studies have explored food security, food system disruption and dietary diversity in the USA (11), China (12), India (29) and Bangladesh (13), during the COVID-19 pandemic. A recent study by Adams et al noted that the number of families from the USA reporting 'very low' scores for food security increased by 20 % from data prior to COVID-19 (11) .…”
mentioning
confidence: 99%